2007
DOI: 10.1002/cvde.200606508
|View full text |Cite
|
Sign up to set email alerts
|

Plasma‐Enhanced Atomic Layer Deposition of Palladium on a Polymer Substrate

Abstract: In this paper, a method for the plasma-enhanced (PE) atomic layer deposition (ALD) of palladium on air-exposed, annealed poly(p-xylylene) (Parylene-N, or PPX) is presented. Palladium is successfully deposited on PPX at 80°C using a remote, inductively coupled, hydrogen/nitrogen plasma with palladium (II) hexafluoroacetylacetonate (Pd II (hfac) 2 ) as the precursor. By optimizing the mixture of hydrogen and nitrogen, the polymer surface is modified to introduce active sites allowing the chemisorption of the Pd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…For the ALD of metals, a wide range of co-reactants have been explored, with gases or plasmas of O 2 , H 2 , and NH 3 being the most common choices. In addition, less common chemicals such as hydrazine (N 2 H 4 ), silane (SiH 4 ), disilane (Si 2 H 6 ), formic acid (CH 2 O 2 ), and tertiary butyl hydrazine (C 4 H 12 N 2 ) have been used. , Moreover, certain ALD processes make use of what can be referred to as an advanced ALD cycle , in which either two or more co-reactants are dosed simultaneously or after one another in an ABC-type manner. For instance, mixed H 2 /N 2 plasmas have been used for the ALD of a variety of materials. Furthermore, Hämäläinen et al deposited Ir, Pd, Rh, and Pt at low temperatures (120–200 °C) using consecutive O 3 and H 2 exposures, and similar ABC-type cycles were later reported for the ALD of Ru (at 150 °C) using subsequent O 2 and H 2 doses and for the ALD of Pt (at room temperature) using subsequent O 2 and H 2 plasmas. …”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…For the ALD of metals, a wide range of co-reactants have been explored, with gases or plasmas of O 2 , H 2 , and NH 3 being the most common choices. In addition, less common chemicals such as hydrazine (N 2 H 4 ), silane (SiH 4 ), disilane (Si 2 H 6 ), formic acid (CH 2 O 2 ), and tertiary butyl hydrazine (C 4 H 12 N 2 ) have been used. , Moreover, certain ALD processes make use of what can be referred to as an advanced ALD cycle , in which either two or more co-reactants are dosed simultaneously or after one another in an ABC-type manner. For instance, mixed H 2 /N 2 plasmas have been used for the ALD of a variety of materials. Furthermore, Hämäläinen et al deposited Ir, Pd, Rh, and Pt at low temperatures (120–200 °C) using consecutive O 3 and H 2 exposures, and similar ABC-type cycles were later reported for the ALD of Ru (at 150 °C) using subsequent O 2 and H 2 doses and for the ALD of Pt (at room temperature) using subsequent O 2 and H 2 plasmas. …”
Section: Introductionmentioning
confidence: 80%
“… 12 , 26 In addition, in the work of Ten Eyck et al, the H 2 /N 2 ratio was optimized in order to maximize the NH x generation in the plasma. 10 Finally, ALD processes for Ru, Ni, and Ag have been reported to improve when NH 3 plasmas are used instead of H 2 plasmas (in terms of a higher GPC and lower resistivity), which also suggests an important role of NH x species present in the NH 3 plasmas. 18 20 …”
Section: Discussionmentioning
confidence: 99%
“…The atomic layer deposition (ALD) is a controlled growth process used to decorate or load the monodispersed metal nanoparticles (NP) at a higher growth rate 16 . It has been shown that the ALD process for the decoration of inorganic (metal or metal oxide) nanostructures on the polymeric support materials facilitate to avoid the agglomeration and detachment of nanostructures for the specific purposes 17 19 . More importantly, the surface decoration of metal NP on the flexible polymeric nanofibrous webs will provide the improvised surface area for the interaction and avoid the issues related to the recoverability and multiple usages.…”
Section: Introductionmentioning
confidence: 99%
“…Using the second approach, McCarthy and Herrera‐Alonso13 reported a method for the chemical surface modification of Parylene films through reactions at the aromatic ring using electrophilic aromatic substitution. The physical methods include plasma treatment,14, 15 and photo‐oxidation in the presence of air,16, 17 which leads to the formation of an oxidized surface layer.…”
Section: Introductionmentioning
confidence: 99%